“It’s Like a Prison without Bars”: Experiences in a Mandatory GED Program - C. Amelia Davis; Ron Mottern; Mary F. Ziegler (Adult Education Research Conference, 2010)
The purpose of this phenomenological research study was to describe how adult students experience a legally coerced GED program in a community alternative to prison program. A phenomenological-hermeneutical approach was used to derive common themes that represented essence of the students’ experiences.